2017
DOI: 10.1002/ccd.27328
|View full text |Cite
|
Sign up to set email alerts
|

Vascular complications after balloon aortic valvuloplasty in recent years: Incidence and comparison of two hemostatic devices

Abstract: VC rate after BAV is fairly low in experienced centers without major differences between the 2 most used VCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Interestingly another conventional collagen‐based vascular closure device (AngioSeal®, St. Jude Medical, St. Paul, Minnesota), used more typically in the context of coronary angiography and intervention, was deployed at the non‐major access site in all cases. A comparison of percutaneous suture‐based VCD with AngioSeal® in the context of balloon aortic valvuloplasty (typically using 9Fr access) reported more frequent minor vascular (3.5% vs 6.9%, P = .042) and less frequent requirement for blood transfusion (6.65 vs 3.5%, P = .034) respectively for the collagen VCD and similar major vascular complications overall . The observations from our series reported here also highlight a potential benefit of using the radial artery systematically as the secondary (nonmajor) access site during TAVR with its inherent lower risk of vascular and bleeding complications demonstrated in the context of coronary interventions (compared to the femoral artery) .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Interestingly another conventional collagen‐based vascular closure device (AngioSeal®, St. Jude Medical, St. Paul, Minnesota), used more typically in the context of coronary angiography and intervention, was deployed at the non‐major access site in all cases. A comparison of percutaneous suture‐based VCD with AngioSeal® in the context of balloon aortic valvuloplasty (typically using 9Fr access) reported more frequent minor vascular (3.5% vs 6.9%, P = .042) and less frequent requirement for blood transfusion (6.65 vs 3.5%, P = .034) respectively for the collagen VCD and similar major vascular complications overall . The observations from our series reported here also highlight a potential benefit of using the radial artery systematically as the secondary (nonmajor) access site during TAVR with its inherent lower risk of vascular and bleeding complications demonstrated in the context of coronary interventions (compared to the femoral artery) .…”
Section: Discussionsupporting
confidence: 54%
“…Compared to percutaneous suture-based devices this novel VCD has a shorter learning curve [15] with no risk of postdeployment stenosis which is seen with suture-based devices and is a potential concern as the scope of TAVR extends to younger, lower risk and more active patients [16,17]. Furthermore, in the series reported here the operators percutaneous suture-based VCD with AngioSeal® in the context of balloon aortic valvuloplasty (typically using 9Fr access) reported more frequent minor vascular (3.5% vs 6.9%, P 5 .042) and less frequent requirement for blood transfusion (6.65 vs 3.5%, P 5 .034) respectively for the collagen VCD and similar major vascular complications overall [18]. The observations from our series reported here also highlight a potential benefit of using the radial artery systematically as the secondary (nonmajor) access site during TAVR with its inherent lower risk of vascular and bleeding complications demonstrated in the context of coronary interventions (compared to the femoral artery) [19,20].…”
Section: Discussionmentioning
confidence: 57%
“…Increased operator skill, growing experience in managing large‐bore vascular accesses, and the use of low‐profile balloons through smaller vascular sheaths are potential explanations. An analysis from two high‐volume centers over 930 BAVs showed that the vascular complication (VC) rate has become relatively low (2.7% major complications) 50 . Nowadays BAV is usually performed using 8–10 Fr arterial sheaths (rather than 13–14 Fr), relying on the use of vascular closure devices because of reduced hemostatic time and a lower rate of VC in comparison with manual compression 51 .…”
Section: Outcomes Of Standalone Bavmentioning
confidence: 99%
“…Nowadays BAV is usually performed using 8–10 Fr arterial sheaths (rather than 13–14 Fr), relying on the use of vascular closure devices because of reduced hemostatic time and a lower rate of VC in comparison with manual compression 51 . Indirect comparisons show no compelling superiority between suture‐ or collagen‐mediated devices 50 . The preclosure technique is widely adopted, sometimes with two devices.…”
Section: Outcomes Of Standalone Bavmentioning
confidence: 99%
“…23 Although the most frequent drawback of BAV was vascular complications caused by largesized sheaths, recently, several types of hemostatic devices have been used effectively. 24 At the present institution we usually use the HemCon® bandage (HemCon Medical Technologies, Portland, OR, USA) for the puncture site of the femoral artery. A total of 67.7% of the present patients underwent the antegrade approach via the femoral vein, and this may be feasible for decreasing vascular complications.…”
Section: Complicationsmentioning
confidence: 99%